Economic and Environmental Implications of Sustainable Agricultural Practices in Arid Regions: A Cross-disciplinary Analysis of Plant Science, Management, and Economics - Lawal, Trimisiyu Omotayo; Abdulsalam, Mustapha; Mohammed, Aliyu; Sundararajan, Shanmugam (International Journal of Membrane Science and Technology, 2023)
This study addresses the pressing challenge of promoting sustainable agricultural practices in arid regions, focusing on their economic and environmental implications. Arid regions face one-of-a-kind challenges because of water scarcity and environmental fragility, necessitating the adoption of practices that guarantee agricultural viability without compromising ecological balance. The study's goal is to lead a complete cross-disciplinary analysis encompassing Plant Science, Management, and Economics, aiming to reveal insight into the intricate relationship between sustainable agricultural practices, economic viability, and environmental preservation. The research issue focuses on identifying viable strategies that harmonize the economic and environmental dimensions of agriculture in arid regions. The exploration of existing studies gives insights into the adoption of innovative technologies, including accurate irrigation systems, drought-resistant crop varieties, and eco-friendly pest management methods. Through the analysis of the gathered data, this study uncovers major patterns and findings regarding the economic feasibility of sustainable practices in arid regions. It integrates the mind-boggling interactions between agricultural efficiency, cost-adequacy, and environmental sustainability. The research culminates in a bunch of recommendations for policymakers, emphasizing the requirement for tailored incentives, information dissemination, and integrated management approaches. In conclusion, this paper highlights the paramount importance of harmonizing economic and environmental dimensions in arid area agriculture through sustainable practices. It also acknowledges the limitations inherent in secondary data analysis and the necessity for further empirical research. The synthesis of insights from Plant Science, Management, and Economics contributes to a holistic understanding of the subject and aligns with the journal's commitment to multidisciplinary research.